Integrating Local Wisdom and Digital Transformation to Strengthen MSME Growth in Indonesian Traditional Markets: Evidence from Solo and Jakarta - Oryza Sativa Heningtyas; Herlina Sunarti; Ahmad Basid; Endang Tri Pujiastuti; Firda Auralin (Indonesian Journal of Taxation and Accounting, 2026)
Purpose – This study examines whether Javanese relational business wisdom (Tuna Sathak Bathi Sanak) and win-win collaboration influence MSME growth in traditional markets, and whether digital transformation moderates these relationships. Methods – A quantitative survey involved 215 MSME actors from Gede Market, Solo (n = 110), and Glodok Market, Jakarta (n = 105). Data were analyzed using multiple linear regression and moderated regression analysis in SPSS 29. Findings – Tuna Sathak Bathi Sanak positively predicted MSME growth (B = .431, β = .490, p < .001), while win-win collaboration was negative and significant (B = -.391, β = -.400, p < .001). Digital transformation had a positive direct effect and strengthened the cultural-value pathway, but the collaboration interaction remained negative. Research implications – Digital capability can translate local relational values into market resilience when supplier collaboration is governed transparently. Originality – The study integrates local wisdom, interfirm collaboration, and digital transformation in an accounting-oriented MSME growth model.